2008
DOI: 10.3390/md6030407
|View full text |Cite
|
Sign up to set email alerts
|

Floridoside Extracted from the Red Alga Mastocarpus stellatus Is a Potent Activator of the Classical Complement Pathway

Abstract: Many biological properties of algae have been found to have useful applications in human health, particularly in the fields of oncology and immunology. Floridoside, extracted from the red alga Mastocarpus stellatus, has a structure similar to the xenoantigen Gal alpha 1-3 Gal. This xenoantigen has been described to induce a high immune response in human xenografts and is mediated by natural anti-gal antibodies that activate the classical complement pathway. Based on this property, we analyzed the potential act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Palmaria palmata contains high amounts of the immunestimulating heteroside-floridoside, which may explain the findings observed in the current study [18]. This compound has a degree of seasonal and locational variability in P. palmata with its contribution ranging between 3 and 25 % of dry weight [40,41].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Palmaria palmata contains high amounts of the immunestimulating heteroside-floridoside, which may explain the findings observed in the current study [18]. This compound has a degree of seasonal and locational variability in P. palmata with its contribution ranging between 3 and 25 % of dry weight [40,41].…”
Section: Discussionsupporting
confidence: 70%
“…Specifically for P. palmata, this anti-inflammatory activity has been attributed to its relatively high proportion of eicosapentaenoic acid (EPA) concentration and its favourably low ω6/ω3 ratio (0.13) [17]. Conversely, P. palmata contains 3-25 % of the immune-stimulating heteroside-floridoside, which has been shown to stimulate inflammation by affecting the innate immune response [18]. Numerous studies have shown that methanol, ethanol and aqueous extracts of P. palmata exhibit antioxidant activity [19][20][21].…”
mentioning
confidence: 99%
“…Therefore, floridoside, an effective osmoregulator that possessed a significant antioxidant capacity (Courtois et al. , Li et al. ), may serve as an antioxidant and protect organelles and macromolecules during heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides can also be extracted from other sources such as algae;, , these represent an important source of polysaccharides and low molecular weight carbohydrates, some of which may show some capacity for immunomodulation. This is the case for 2‐ O ‐α‐ d ‐galactopyranosylglycerol, also called floridoside ( 1 ; Figure ), which is extracted from Rhodymenia palmate or Mastocarpus stellatus . Courtois et al have shown that floridoside is a mediator in the classical complement pathway, and that it causes the recruitment and activation of natural immunoglobulin M (IgM) .…”
Section: Introductionmentioning
confidence: 99%